Change in the gender division of domestic work after mothers or fathers took leave: exploring alternative explanations. Issue 1 (1st January 2019) - Schober, Pia S.; Zoch, Gundula
ABSTRACT: This study investigates how the durations of childcare leaves taken by mothers and fathers in Germany relate to the gender division of housework and childcare after labour market return. It examines to what extent changes in economic resources because of leave take-up may account for adaptations in the division of domestic work of dual-earner couples. Using data from the German Socio-Economic Panel (1992–2012) on about 800 couples with a first or second birth, we applied OLS regression models with lagged dependent variables. The results suggested that dual-earner couples where mothers took longer leaves experienced a greater shift towards a gender-traditional division of domestic labour after childbirth. Fathers' leave take-up was associated with a more equal division of family work. Lower relative earnings, e.g. as a result of changes in job-related skills after the leave, did not account for the shift in the gender division of family work.